Ravulizumab in Myasthenia Gravis: A Review of the Current Evidence - Vu T; Wiendl H; Katsuno M; Reddel SW; Howard JF Jr (Neuropsychiatric Disease and Treatment, 2023)
Tuan Vu,1 Heinz Wiendl,2 Masahisa Katsuno,3 Stephen W Reddel,4 James F Howard Jr5 1Department of Neurology, University of South Florida Morsani College of Medicine, Tampa, FL, USA; 2Department of Neurology with Institute of Translational Neurology, University Hospital Münster, Münster, Germany; 3Department of Neurology, Nagoya University Graduate School of Medicine, Nagoya, Japan; 4Department of Neurology, Concord Hospital, University of Sydney, Sydney, NSW, Australia; 5Department of Neurology, The University of North Carolina, Chapel Hill, NC, USACorrespondence: Tuan Vu, Department of Neurology, University of South Florida Morsani College of Medicine, 13220 USF Laurel Drive, Tampa, FL, 33612, USA, Tel +1 813 396 2955, Email tvu6@usf.eduAbstract: The terminal complement C5 inhibitor ravulizumab was engineered from the humanized monoclonal antibody eculizumab to have an extended half-life and duration of action. It binds to human terminal complement protein C5, inhibiting its cleavage into C5a and C5b, thus preventing the cascade of events that lead to architectural destruction of the postsynaptic neuromuscular junction membrane by the membrane attack complex, and consequent muscle weakness in patients with anti-acetylcholine receptor (AChR) antibody-positive generalized myasthenia gravis (gMG). The 26-week randomized, placebo-controlled period (RCP) of the phase 3 CHAMPION MG study demonstrated the rapid efficacy of ravulizumab in reducing MG symptoms. Weight-based dosing of ravulizumab every 8 weeks provided sustained efficacy, in terms of patient-reported (Myasthenia Gravis–Activities of Daily Living) and clinician-reported (Quantitative Myasthenia Gravis) endpoints in patients with anti-AChR antibody-positive gMG. Pharmacokinetic and pharmacodynamic analyses showed therapeutic serum ravulizumab concentrations (> 175 μg/mL) were achieved immediately after the first dose and were maintained throughout 26 weeks, irrespective of patient body weight; inhibition of serum free C5 was immediate, complete (< 0.5 μg/mL), and sustained in all patients. Interim results from the open-label extension (OLE) showed that after 60 weeks, efficacy was maintained in patients continuing on ravulizumab. Rapid and sustained improvements in efficacy, similar to those seen in patients initiating ravulizumab in the RCP, were observed after initiation of ravulizumab treatment in patients who switched from placebo in the RCP to ravulizumab in the OLE. The findings from the RCP and OLE support ravulizumab’s favorable safety profile. In conclusion, ravulizumab has a simple weight-based administration and long dosing interval. Its targeted mechanism of action without generalized immunosuppression is reflected in its rapid onset of symptom improvement, sustained efficacy and good safety profile in the treatment of patients with anti-AChR antibody-positive gMG.Plain Language Summary: Ravulizumab in anti-AChR antibody-positive gMGRavulizumab was engineered from eculizumab to have an extended half-life and longer duration of action. It binds to terminal complement protein C5 to inhibit anti-AChR antibody-mediated activation of terminal complement and destruction of the neuromuscular junction.Pharmacokinetic/pharmacodynamic analyses support a simple weight-based administration and long dosing interval and show that therapeutic ravulizumab concentrations and complete inhibition of C5 were achieved immediately after the first dose.The 26-week randomized placebo-controlled period (RCP) of the CHAMPION MG study in patients with anti-AChR antibody-positive gMG showed that ravulizumab has rapid and sustained efficacy with good safety and tolerability across a broad range of patients.Ravulizumab’s efficacy, safety, and tolerability were confirmed in interim analyses of the open-label extension study (including data for up to 60 weeks from the RCP baseline): efficacy was maintained in patients remaining on ravulizumab; rapid and sustained efficacy was established in patients switching from placebo to ravulizumab.Keywords: acetylcholine receptor antibody, complement, membrane attack complex, monoclonal antibody, terminal complement complex